Behandlung der Psoriasis mit Secukinumab: Praxisrelevante Hinweise - Körber, Andreas; Augustin, Matthias; Behrens, Frank; Gerdes, Sascha; von Kiedrowski, Ralph; Schäkel, Knut; Sticherling, Michael; Wilsmann-Theis, Dagmar; Wohlrab, Johannes; Simon, Jan Christoph (Hautarzt, 2021)
Background: Moderate to severe plaque psoriasis can be treated effectively with immunomodulating biologicals such as the interleukin-17A inhibitor secukinumab. In practice, however, questions often arise as to how to proceed in special situations, such as infections, comorbidity, pregnancy, or surgery. Objectives: To address frequent questions about the treatment of plaque psoriasis with secukinumab in a consensus document of German psoriasis experts that supplements current guidelines. Methods: In a virtual expert meeting in May 2020, practical aspects of the treatment of psoriasis were discussed based on the experience of the participants and on current literature. The results of this discussion were summarized in the present consensus document. Results: This article provides practical guidance on case history, documentation of previous therapies, severity of psoriasis, and comorbidities before starting therapy with secukinumab. For patients treated with secukinumab, the course of action in case of vaccinations, chronic or acute infections, surgical interventions, special manifestations of psoriasis, and comorbidities including history of cancer and autoimmune disorders is discussed. Questions regarding family planning and health policy regulations are also addressed. Discussion: The recommendations for the treatment of psoriasis with secukinumab summarized in this consensus document may contribute to achieve optimal therapy for patients and to improve their quality of life.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Biological products; Comorbidity; Infections; Perioperative management; Special situations